2018
DOI: 10.1016/s1470-2045(18)30078-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of body-mass index and outcomes in patients with metastatic melanoma treated with targeted therapy, immunotherapy, or chemotherapy: a retrospective, multicohort analysis

Abstract: Background Obesity has been linked to increased mortality in several cancer types; however, the relationship between obesity and survival in metastatic melanoma is unknown. The aim of this study was to examine the association between BMI, progression-free survival (PFS), and overall survival (OS) in metastatic melanoma. Methods This study included 6 independent cohorts for a total of 1918 metastatic melanoma patients. These included two targeted therapy cohorts [randomized control trials (RCTs) of dabrafenib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
459
11
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 549 publications
(543 citation statements)
references
References 33 publications
26
459
11
5
Order By: Relevance
“…In addition, the the rising obesity epidemic in the U.S. has led to increase use of NSAIDs and other medications, which has important implications in the outcomes of patients with melanoma. A study from our groups demonstrated a significant survival benefit for obese men who were treated with immunotherapy and targeted therapy, which perhaps could be confounded by concurrent medication . However, we did not observe a clear contributor to such an association in this study.…”
Section: Discussioncontrasting
confidence: 75%
“…In addition, the the rising obesity epidemic in the U.S. has led to increase use of NSAIDs and other medications, which has important implications in the outcomes of patients with melanoma. A study from our groups demonstrated a significant survival benefit for obese men who were treated with immunotherapy and targeted therapy, which perhaps could be confounded by concurrent medication . However, we did not observe a clear contributor to such an association in this study.…”
Section: Discussioncontrasting
confidence: 75%
“…57 Even more perplexing is the recent report that increasing BMI in male melanoma patients correlates with improved response to immunotherapy, regardless of the extent of obesity. 58 The biological basis for this intriguing clinical observation is not clear, nor is it known whether the protective effect of obesity is specific to melanoma. However, it is worth noting that many obese male melanoma patients in this clinical study received anti-diabetic drugs, 58 which have been shown to enhance the antitumor activity of anti-PD-1 blockade in preclinical melanoma models.…”
Section: Discussionmentioning
confidence: 99%
“…15 There are several proposed explanations for the observation that higher BMI is associated with improved overall Figure 1 The effects of body mass index across the cancer continuum. 29 Moreover, in a pooled analysis of solid and hematologic malignancies, sex-stratified analysis demonstrated that a BMI ≥25 kg/m 2 was associated with improved overall survival in males [HR: 0.82; P = 0.003] but not in females [HR: 1.04; P = 0.86]. The interval along the cancer continuum where the higher body mass index begins to switch from a deleterious risk factor to an advantageous risk factor, and why, is not yet known.…”
Section: Body Mass Indexmentioning
confidence: 99%